Characterization of Indoor Molds after Ajka Red Mud Spill, Hungary - Magyar Donát; Tischner Zsófia; Szabó Bence; Freiler-Nagy Ágnes; Papp Tamás; Allaga Henrietta; Kredics László (2024)
A red mud suspension of ~700,000 m3 was accidentally released from the alumina plant in Ajka, Hungary, on the 4th of October 2010, flooding several buildings in the nearby towns. As there is no information in the literature on the effects of red mud on indoor mold growth, we conducted studies to answer the following question: does the heavy metal content of red mud inhibit fungal colonization in flooded houses? In order to gain knowledge on fungal spectra colonizing surfaces soaked with red mud and on the ability of fungi to grow on them, swabs, tape lifts, and air samples were collected from three case study buildings. A total of 43 fungal taxa were detected. The dominant species were Penicillium spp. on plaster/brick walls, but Aspergillus series Versicolores, Cladosporium, Acremonium, and Scopulariopsis spp. were also present. The level of airborne penicillia was high in all indoor samples. Selected fungal strains were subcultured on 2% MEA with 10−1 and 10−4 dilutions of red mud. The growth rate of most of the strains was not significantly reduced by red mud on the artificial media. The consequences of similar industrial flooding on indoor molds are also discussed in this paper.
Keywords: Biológiai tudományok